2016
DOI: 10.1080/15582159.2016.1157782
|View full text |Cite
|
Sign up to set email alerts
|

Parents, Homevoters, and Public School Employees: An Analysis of Voting Patterns in the 2012 Georgia Charter Schools Amendment Referendum

Abstract: Georgia's 2012 Charter Schools Amendment was the first successful statewide school choice referendum in the United States. This amendment permitted the state to authorize new charter schools, thereby creating a way for charter creators to bypass local school boards. This study analyzes voting on this state constitutional amendment and finds that support was higher among counties with lower achieving public schools, more school-aged children, more adults having college degrees, more private school enrollment, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Corcoran and Stoddard (2011) found a partisan division regarding support for charter school referenda: voters who supported Republican candidates were more likely to support charter school referenda. Collingwood, Jochim, and Oskooii (2018) and Conaway, Scafidi, and Stephenson (2016) also acknowledged the importance of ideology, but they found different results. Collingwood, Jochim, and Oskooii (2018) concluded that partisan division was not significant in the 2012 referendum in Washington State.…”
Section: Trends In Charter School Support and Oppositionmentioning
confidence: 99%
See 4 more Smart Citations
“…Corcoran and Stoddard (2011) found a partisan division regarding support for charter school referenda: voters who supported Republican candidates were more likely to support charter school referenda. Collingwood, Jochim, and Oskooii (2018) and Conaway, Scafidi, and Stephenson (2016) also acknowledged the importance of ideology, but they found different results. Collingwood, Jochim, and Oskooii (2018) concluded that partisan division was not significant in the 2012 referendum in Washington State.…”
Section: Trends In Charter School Support and Oppositionmentioning
confidence: 99%
“…The last study of predictors of public support for charter school referenda was conducted by Conaway and her colleagues. Conaway, Scafidi, and Stephenson (2016) studied the details of the 2012 Georgia Charter Schools Amendment Referendum. As of fall 2018, the 2012 Georgia Charter School Amendment Referendum was the only successful charter school referendum.…”
Section: Trends In Charter School Support and Oppositionmentioning
confidence: 99%
See 3 more Smart Citations